Детские годы. Повести русских писателей - Почтенная К. (Всемирная детская библиотека, 2004)
Экземпляры: аб. (2005) / Инвентарный номер: 48772 / Цена: / Сис.шифр: 84(2Рос=Рус)1 / Авт.знак: Д 38 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)1